Using clinical practice guidelines to manage dengue: a qualitative study in a Malaysian hospital - Wharton-Smith, Alexandra; Green, Judith; Loh, Ee Chin; Gorrie, Alexander; Omar, Sharifah Faridah Syed; Bacchus, Loraine; Lum, Lucy Chai See (BMC, 2019)
Background: Malaysia has rising dengue incidence. World Health Organization clinical practice guidelines for managing dengue have been adapted by the Ministry of Health in Malaysia, with evidence of good awareness by clinicians. However, dengue mortality has not reduced. This study aimed to explore the challenges of dengue management for Medical Officers, with a particular focus on use of clinical practice guidelines. Methods: Qualitative study using six focus groups and 14 semi-structured interviews with doctors responsible for dengue management at a large tertiary hospital in Malaysia. Results: Dengue was recognised as difficult to diagnose and manage. Wide awareness and use of both WHO and Ministry of Health guidelines was reported, but several limitations noted in their coverage of particular patient groups. However, the phrase 'guidelines' also referred to local algorithms for fluid management, which were less clinically evidence-based. Where Medical Officers were well trained in the appropriate use of evidence-based guidelines, barriers to use included: the potential for 'following the algorithm' to undermine junior clinicians' claims to clinical expertise; inability to recognise the pattern of clinical progress; and lack of clinical experience. Other reported barriers to improved case management were resource constraints, poor referral practices, and insufficient awareness of the need for timely help seeking. Conclusions: Awareness of clinical practice guidelines is a necessary, but not sufficient, condition for optimal dengue management. In high prevalence settings, all clinical staff would benefit from regular dengue management training which should include diagnosis, practice in monitoring disease progression and the use of clinical practice guidelines in a range of clinical contexts. © 2019 The Author(s).